Quality of Life as Medicine: A Pilot Studyof Patients with Chronic Illness and Pain - Soren Ventegodt; Joav Merrick; JØrgen Anderson (The Scientific World Journal)
An intensive 5-day quality-of-life (QoL) session was constructed based on a psychosomatic model. The session was comprised of teaching on philosophy of life, psychotherapy, and body therapy. The three elements were put together in such a way that they mutually supported each other. The synergy attained was considerable. The pilot study demonstrated that in the course of only 1 week, patients had time to revise essential life-denying views and to integrate important, unfinished life events involving negative feelings. Consequently, the patients became more present in the body’s blocked-off areas and subjectively healthier. Nineteen persons with chronic illness and pain (fibromyalgia, chronic tiredness, whiplash, mild depression, and problems involving pain in arms and legs including osteoarthritis), and unemployed for 5–7 years attended the course. In the week before and after the 5-day course, the participants completed the validated SEQOL (Self-Evaluation of Quality of Life Questionnaire) including questions on self-evaluated health and the unvalidated “Self-Evaluation of Working-Life Quality Questionnaire” (SEQWL). This pilot study was without a control group or clinical control. As far as diagnoses were concerned, the group was inhomogeneous. Common for the group was a low QoL, poor quality of working life QWL, and numerous health problems. The study showed an 11.2% improvement in QoL (p < 0.05), a 6.3% improvement in QWL (p < 0.05), and a 12.0% improvement in self-perceived physical health (p = 0.08). There was a 17.3% improvement in self-perceived psychological health (p < 0.05) and satisfaction with health in general improved by 21.4% (p < 0.05). Symptoms like pain were almost halved and several of the participants were free of pain for the first time in years. In conclusion it seemed that the combination of training in philosophy of life, psychotherapy, and body therapy can give patients a large, fast, and efficient improvement in QoL, QWL, and health. It is not known if these changes will be permanent and if all kinds of patients with different health problems will gain from this cure. Further research should be conducted.